Social inclusion: an analysis of public social inclusion policies applied in the City of Dianópolis/TO (Research, Society and Development, 2020)
This paper aims to present a relationship between public policies and the social inclusion of children and adolescents from Dianópolis, Tocantins. The study was conducted through an interview with (50) parents of children, adolescents and two public managers in the municipality. The research is exploratory, descriptive, bibliographic and field. The methods employed were; quantitative and qualitative. The instruments of data collection were three structured questionnaires with open and closed questions, classified as: A-B-C. The interviews were carried out from April 2nd to June 30th, 2018. Through the research it was possible to identify three projects that can be characterized as public policies of social inclusion: sports initiation project in the field of football, the Escola de Futebol Zé de Rosa, which serves 100 children and adolescents; the English with Citizenship project, which offers English language classes for students from the 7th to the 9th grade of elementary school with 64 children and adolescents enrolled. The Language Center Project, carried out by the Dianópolis Regional Teaching Directorate, currently serves 680 students from 11 years of age.